INTERNAL QUALITY AND FUNCTIONAL PROPERTIES OF KAMPUNG CHICKEN EGGS IMMERSED WITH WATER EXTRACT OF RED KIDANG BANANA PEEL (Musa Acuminata Red Dacca) - Fahreza Helmi Isnaini; Vivin Andriani; Tatang Sopandi (Seminar Nasional Hasil Riset dan Pengabdian, 2024)
Preserving eggs using environmentally friendly technology is very useful in conditions without refrigeration facilities. The study investigated how the internal quality and functional characteristics of kampung chicken eggs are affected by immersion in Musa Acuminata Red Dacca banana peel water extract. A completely randomized experimental design was used for the investigation, and four treatments—one for each concentration of banana peel water extract were repeated five times. The results showed that immersing in banana peel water extract at a concentration of 40% was substantial (P<0.05) to slenderize, changes in air sac, egg yolk and albumen index, egg foam capability, and stability. This study concludes that immersing in 40% water extract of Musa Acuminata Red Dacca banana peel can maintain internal quality and functional properties and preserve kampung chicken eggs for 30 days at ambient temperature. Keywords: internal quality, banana peel, functional properties, eggs.